HUMAN RESOURCE MANAGEMENT STRATEGY AND TEACHER PERFORMANCE IN IMPROVING LEARNING EFFECTIVENESS AT MAN 2 PANDEGLANG - Suryapermana, Nana; Rahmatullah, Mamat (Yayasan Education and Social Center, 2025)
This study aims to analyze human resource (HR) management strategies and teacher performance in improving learning effectiveness at MAN 2 Pandeglang. The study used a qualitative case study approach, involving the principal, the vice principal of curriculum, teachers, and education staff as informants. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using NVivo with open, axial, and selective coding techniques. The results showed that HR management strategies in the madrasah have been implemented in a structured manner, including teaching load planning, teacher professional development, academic supervision, and appreciation. However, these strategies have not been based on an in-depth analysis of learning needs, so their contribution to learning quality remains partial. Teacher performance meets administrative standards, but learning implementation remains limited to lecture-based methods, and evaluations are more focused on cognitive aspects. Learning effectiveness is in the sufficient category, with a conducive classroom climate, but student engagement and method variety need improvement. This study confirms that integrating HR management strategies and teacher performance development is key to creating more effective, adaptive, and innovative learning.